How booking.com's brand identity compares to its brand image - Crespo, María De Las Nieves Rojas (2020)
This paper studies Booking.com brand’s identity and how it compares to its brand image. Kapferer Brand Identity Prism (2008) is used to identify the main brand elements that build the identity. Once defined, the comparison with the customer’s opinion is done using a sample of 12Portuguese, men and women, collected conducting a qualitative research. The main brand attributes are not always equally perceived by the consumer. That is why it is concluded that in today’s constantly changing reality, some of thebrand identity facets aremore dynamic and should be adapted to meet the new customer desires that changes over time.